RETRACTED: Autoantibodies in Renal Diseases – Clinical Significance and Recent Developments in Serological Detection - Mastroianni-Kirsztajn, Gianna; Hornig, Nora; Schlumberger, Wolfgang (Frontiers in Immunology, 2015)
Autoimmune dysfunctions are the “bête noire” in a range of debilitating nephropathies. Autoimmune-mediated damage to the kidneys can be triggered by autoantibodies directed against specific proteins or renal structures, for example the phospholipase A2 receptor or the glomerular basement membrane, resulting in glomerular diseases such as primary membranous nephropathy or Goodpasture’s disease. Moreover, secondary damage to the kidney can be part of the wide-reaching effects of systemic autoimmune diseases such as vasculitis or systemic lupus erythematosus (SLE) – the latter counts lupus nephritis among its most severe manifestations. Systemic autoimmune diseases are characterized by non-organ-specific autoantibodies, directed for example against neutrophil cytoplasmic antigens in systemic vasculitis and against double-stranded DNA and nucleosomes in SLE. A large variety of innovative and highly specific and sensitive autoantibody tests have been developed in the last years that are available to identify autoimmune kidney diseases at an early stage. Thus, serological in vitro diagnostics allow for appropriate interventional therapy in order to prevent disease progression often resulting in need of dialysis and transplantation.